In vitro antibacterial activity of various adhesive materials against oral streptococci. Issue 1 (2nd January 2016) - Ozel, Emre; Kolayli, Fetiye; Tuna, Elif Bahar; Er, Doganhan
ABSTRACT: The purpose of this study was to investigate the antibacterial activity of various adhesive materials against five different oral streptococci. The antibacterial activity of the adhesive systems was evaluated using agar diffusion tests. In each section of each plate, 6-mm-diameter wells were created with sterilized glass cylinders. Ten microlitres of self-etch adhesives and control materials were applied into the shallow holes. After incubation at 37 °C for 24 h, the growth inhibition zones were measured in millimetres. Statistical analyses were performed by using two-way analysis of variance and the Tukey's multiple range test ( p < 0.05). A statistically significant difference was found between inhibition zones of oral streptococci cultivated with different adhesive systems ( p < 0.01). Clearfil Protect Bond exhibited larger inhibition zones than the other materials that were used against the oral streptococci. The antibacterial effects observed for the different tested adhesive systems may be related to 12-methacryloyloxy dodecyl-pyridinium bromide and the acidic nature of the materials.